Characteristics of PB 260 clone rubber coagulated with natural coagulants: type of Averrhoa - Achmad, Feerzet; Deviany, Deviany; Yuniarti, Reni; Fikrah, Faizatul; Az-Zahra, Syifa; Qarimah, Akhlatul; Marlina, Titi; Tambunan, Yonathan Marasi; Rahmadini, Gustia; Damayanti, Damayanti; Suhartono, Suhartono; Suharto, Suharto (Konversi, 2024)
The aim of this research was to determine the properties of the PB 260 clone rubber using the Averrhoa type coagulant. The natural coagulants used in this study were Averrhoa bilimbi and Averrhoa carambola. The latex used was 150 ml of PB 260 clone rubber with a concentration of 100% natural coagulant of 75 ml and 2% formic acid. The rubber properties that were tested were Po, PRI, DRC, ash content, dirt content, volatile matter content and Mooney viscosity. This research also uses a special treatment in the form of centrifugation speed. The higher the centrifugation speed, the higher the pH value of the natural coagulant and the lower the H+ ion value, which accelerates the coagulation time of the latex. In natural coagulant extract, the highest values of Po, PRI, DRC, ash content, dirt content and Mooney viscosity were obtained at 0 rpm for Averrhoa bilimbi extract with values of 40%, 94.17%, 32.83%, 0, 32%, 0.038% and 77 MU. Meanwhile, in the test for volatile matter content, the highest value was found in Averrhoa carambola at 5000 rpm with a value of 0.23%.